Phenothiazine‐Functionalized Poly(norbornene)s as High‐Rate Cathode Materials for Organic Batteries. Issue 9 (28th January 2020) - Otteny, Fabian; Studer, Gauthier; Kolek, Martin; Bieker, Peter; Winter, Martin; Esser, Birgit
Abstract: Organic cathode materials are handled as promising candidates for new energy‐storage solutions based on their transition‐metal‐free composition. Phenothiazine‐based polymers are attractive owing to their redox potential of 3.5 V vs. Li/Li + and high cycling stabilities. Herein, three types of poly(norbornene)s were investigated, functionalized with phenothiazine units through either a direct connection or ester linkages, as well as their crosslinked derivatives. The directly linked poly(3‐norbornylphenothiazine)s demonstrated excellent rate capability and cycling stability with a capacity retention of 73 % after 10 000 cycles at a C‐rate of 100 C for the crosslinked polymer. The polymer network structure of the crosslinked poly(3‐norbornylphenothiazine) was beneficial for its rate performance. Abstract : Fast charging : Poly(norbornene)s, functionalized with phenothiazine units through either a direct connection or ester linkages, are tested as cathode‐active battery materials. Directly linked poly(3‐norbornylphenothiazine) demonstrates excellent rate capability and cycling stability with a capacity retention of 73 % after 10 000 cycles at a C‐rate of 100 C.